2022
DOI: 10.1177/17479541211069935
|View full text |Cite
|
Sign up to set email alerts
|

Small-sided games do not replicate all external and internal loads of a football match-play during pre-season: A case study

Abstract: This study investigated the differences in external and internal load during pre-season training sessions carried out with different SSGs and a friendly match in top-class professional football players. The study was conducted over a full pre-season. Participants were 9 male top-class professional football players (25 ± 5 years; 74 ± 8 kg; 177 ± 8 cm). The following variables were measured: training session duration (min), average heart rate (bpm), total distance (m), distance covered per minute (m/min), the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…As such, the match context, including the initial formation, tactical strategies regarding the distribution of spaces, and ball possession, must also be considered [4,31]. Few existing studies examining the initial formation of the game reported higher demands for Ac/Dec when distances are shorter and fewer players are available [32], especially in possession-based playing styles like the 3-4-2-1 or 4-4-2 formation [33,34]. Positional differences in Ac/Dec demands lack consensus, with some studies suggesting midfielders [3,11,24], others forwards [1], and still others wingers and full-backs [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the match context, including the initial formation, tactical strategies regarding the distribution of spaces, and ball possession, must also be considered [4,31]. Few existing studies examining the initial formation of the game reported higher demands for Ac/Dec when distances are shorter and fewer players are available [32], especially in possession-based playing styles like the 3-4-2-1 or 4-4-2 formation [33,34]. Positional differences in Ac/Dec demands lack consensus, with some studies suggesting midfielders [3,11,24], others forwards [1], and still others wingers and full-backs [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the global indicator of workload (work ratio and player load) was higher during SSGs than in friendly matches. More recently, Pinheiro et al [ 12 ] stated that with professional soccer players the total distance per minute was higher during friendly matches than during different formats of SSGs. Additionally, no differences were found between friendly matches and SSGs considering mechanical values (number and average distance of accelerations).…”
Section: Introductionmentioning
confidence: 99%